The impact of cannabis and methamphetamine use on clinical and functional aspects of outcome in first-episode Schizophrenia patients : a longitudinal study - Scheffler, Frederika (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.